PENERAPAN LATIHAN PLYOMETRIC TERHADAP PENINGKATAN JUMPING SPIKE DALAM PERMAINAN BOLA VOLI - Muhamad Iqbal; Dedi Iskandar (Journal of Physical Education and Sport Science, 2020)
The purpose in this study is to determine the application of plyometric exercises to increase jumping spike in men's volleyball games in extracurricular activities at SMA Negeri 1 Luragung. The method in this study is quantitative to quantitative. Often called traditional methods, quantitative methods are often referred to as new methods, because this method has been used for a long time. This method is called a quantitative method. This study used a pre-experimental design, namely One Group Pre-test-Post test Design. The population in this study were male volleyball extracurricular students at SMA Negeri 1 Luragung, the sample technique applied in this study was total sampling, which means that all populations were sampled, namely 17 students. The instrument used in the upright jumping test study was given streatment or plyometric exercises before the test was carried out. In this study using data analysis techniques for normality test, homogeneity test, and hypothesis test using the T test. When compared, it can be seen that the t value (3.1914> 2.12) t table then H0 is rejected. With the rejection of H0, it can be concluded that there is an increase in the application of plyometric exercises to increase jumping spike in men's volleyball games in extracurricular activities.